HUBUNGAN KARAKTERISTIK PETANI TERHADAP KEBERHASILAN USAHATANI JAGUNG - Bambang Arita; Andri Amaliel Managanta; Ita Mowidu (Universitas Sebelas Maret, 2022)
Corn is an important food commodity after rice. Corn is used as food, animal feed, and industrial raw materials. The increase in harvested area is due to the increase in demand for corn from year to year. This study aims to determine the relationship between farmer characteristics and the success of corn farming and how much income is corn farmers in Dataran Bugi Village Tojo District Tojo Una-Una Regency. This study uses a survey method with descriptive correlational analysis. The results showed that land area and social capital are important factors in increasing the production and income of corn farmers in Dataran Bugi Village Tojo District Tojo Una-Una Regency. The average cost incurred by corn farmers is IDR 3,905,567/growing season and the average farmer income is IDR 14,912,433/growing season. Corn farming in Dataran Bugi Village is feasible with an R/C Ratio of 4.82